The collective need to be inside, the individual spectacle of the outer: Critical Discourse Analysis of the construction of discursive representations about transvestites on Argentinean television - Soich, Matías (2016)
For many decades, the Argentinean travesti (transvestite) community has suffered appalling life conditions due to discrimination, social exclusion and (until the enacting of the Gender Identity Law) official denial of their identities. Using qualitative methodology and from the frame of Critical Discourse Analysis (CDA), this article studies how some Argentinean television programmes from 1993 to 2010 constructed discursive representations about travestis. The analysis reveals two opposing combinations of linguistic resources (strategies) regarding the State abuses suffered by the travestis, their need for social inclusion and their collective fight for their human rights: while the travestis who participate in the programmes reinforce these aspects, the television presenters systematically mitigate them. The discursive representations thus built by the programmes tend to maintain a ‘postmodern’ status quo, which could explain why the Argentinean Gender Identity Law was not accompanied, in 2012, by a public debate as resounding as the one that accompanied same-sex marriage in 2010.